Effects of Electromagnetic Fields (EMF)Near High Voltage Transmission Line: a Case Study (Bangladesh Journal of Medical Physics, 2015)
Abstract not availableBangladesh Journal of Medical Physics Vol.7 No.1 2014 66-68